Effects of cluster nursing on cardiac function and quality of life in coronary heart disease patients with chronic heart failure: A protocol of randomized controlled trial. Issue 14 (8th April 2022) - Jin, Qian; Zhou, Yi; Yin, Delu; He, Hong; Liu, Yonghua; Wu, Yiling
Abstract: Background: Coronary heart disease (CHD) chronic heart failure has high morbidity and mortality, which poses a serious threat to patients' quality of life and life safety. For the treatment of chronic heart failure of CHD, in addition to drugs, high quality nursing measures are also very important. Cluster nursing is a high-quality nursing model based on evidence-based evidence. There is no clinical study to evaluate the effect of cluster nursing on cardiac function and quality of life of CHD patients with chronic heart failure. Methods: This is a prospective randomized controlled trial to investigate the effects of cluster nursing on cardiac function and quality of life in patients with CHD chronic heart failure. Approved by the Clinical Research Ethics Committee of our hospital, patients will be randomly assigned to either routine nursing or cluster nursing. They will be followed up for 3 months after 4 weeks of treatment. Observation indicators include: The total effective rate of cardiac function improvement, Minnesota Living with Heart Failure Questionnaire, left ventricular ejection fraction, N-terminal pro-brain natriuretic peptide, 6-minute walk test, adverse reaction, etc. Data were analyzed using the statistical software package SPSS version 25.0. Discussion: This study will evaluate the effects of cluster nursing on cardiac function and quality of life of CHD patients with chronic heart failure. The results of this study will provide clinical basis for establishing reasonable and effective nursing programs for CHD patients with chronic heart failure.